2008
DOI: 10.1111/j.1365-2702.2007.02276.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring supportive care for individuals affected by Huntington disease and their family caregivers in a community setting

Abstract: It is helpful to allow patients control over timing and frequency of contact with professionals. Improving understanding of the condition in the public and health professionals may enable patients to access a greater range of social activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…Different levels of care are required as the disease progresses, from symptomatic therapy, psychological support to patients and caregivers, to genetic counseling to family members and, ultimately, to palliative care [6][7][8] . This study shows that centers responsible for managing patients with HD throughout SA are committed to providing, mostly in free-of-cost settings, the best level of care possible, as attested by the fact that most institutions have multidisciplinary teams capable of tailoring treatment strategies to individual patient needs.…”
Section: Discussionmentioning
confidence: 99%
“…Different levels of care are required as the disease progresses, from symptomatic therapy, psychological support to patients and caregivers, to genetic counseling to family members and, ultimately, to palliative care [6][7][8] . This study shows that centers responsible for managing patients with HD throughout SA are committed to providing, mostly in free-of-cost settings, the best level of care possible, as attested by the fact that most institutions have multidisciplinary teams capable of tailoring treatment strategies to individual patient needs.…”
Section: Discussionmentioning
confidence: 99%
“…The information inherent in a presymptomatic test result may have long-term implications for the mental health of the patient. Deleterious mutation test results may, for example, result in hypervigilance about symptoms (Soltysiak, Gardiner, & Skirton, 2008), and such testing is usually accompanied by supportive nursing care to facilitate decision making and to help patients and their families make adjustments after the result is known. Feelings of genetic vulnerability may relate to fear of discrimination that could have an impact on self-esteem, personal relationships, employment, health care, and financial stability, and nurses should be aware that these fears may influence decisions about accessing presymptomatic testing for a genetic condition.…”
Section: Genetic Testing: Expanded Use and Examples In Clinical Settingsmentioning
confidence: 99%
“…Despite numerous recommendations for increased and tailored HD carer support (Skirton et al, 2010;Dawson et al, 2004;Soltysiak et al, 2008;Williams et al, 2012;Hartelius et al, 2010), there is a paucity of research describing specific interventions for HD carers and evaluation studies of such interventions. One paper identified that an HD day service was felt to be supportive to carers, promote their well-being and allow respite for them (Soltysiak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One paper identified that an HD day service was felt to be supportive to carers, promote their well-being and allow respite for them (Soltysiak et al, 2008). Another study, involving intensive MDT input provided education sessions for family members, but no evaluation of the impact that this intervention had on carers was undertaken (Piira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%